Quantitative Monitoring of Coastal Erosion and Changes Using Remote Sensing in a Mediterranean Delta - Khaled Mahmoud Abdel Aziz (Civil Engineering Journal, 2024)
The morphology of coastal regions is continually changing because of both natural and human factors. Monitoring and understanding these changes are essential for efficient coastal management and sustainable development. To protect and develop beaches, quantitative monitoring of coastal changes is crucial. According to this study, there is a persistent erosion issue with the shoreline of the Rosetta region in Egypt. Over the previous century, there has been noticeable erosion. This is mostly because of the Aswan High Dam, which was built in 1964 and decreased runoff and sediment flow. Five Landsat images spanning the years 1980–2023 were utilized in this study. The Nile Delta would be eroding at an alarming rate if action were not taken due to coastal erosion, which is made worse by sea level rise. Our study's primary goal is to evaluate the shoreline of the Rosetta region and identify rates of erosion and accretion as well as patterns of accumulation and erosion using a combination of statistical analysis of the coastline using DSAS software and remote sensing techniques. It also seeks to pinpoint hotspots that require security. In this study, the Shoreline Linear Regression Rate (LRR), End Point Rate (EPR), Shoreline Change Envelope (SCE), and Net Shoreline Movement (NSM) were determined by creating cross-sections perpendicular to the baseline using the Digital Shoreline Analysis System (DSAS). According to the analysis of coastal change, the periods with the highest levels of erosion were between 1980 and 1990, before the protection of the promontory took place. In addition, the results extracted from this study showed a stabilized shoreline between 2000 and 2023 at the Rosetta Promontory and noticeable erosion in the east and west of the promontory. Doi: 10.28991/CEJ-2024-010-06-08 Full Text: PDF